SHODHANA FROM THE PERSPECTIVE OF UTPATTI-STHANA OF VYADHI (AYUSHDHARA, 2020)
According to Ayurvedic literature, there are three types of Doshas (Vata, Pitta, Kapha) in the body. These are present predominantly in certain places of the body and such places are known as Vishesha Sthana (Udbhvasthana) and the remaining are identified as Anya Sthana (general site). On the basis of three Dosha, Acharya classified Udbhvasthana into two, in which Pakwashaya is the Udbhvasthana for Vata. Adho Amashaya is the Udbhavasthana for Pitta and Urdhwa Amashaya is the Udbhavasthana for Kapha, and on the basis of these two Udbhava sthana Acharya classifies Shodhan into two in which Vamana is for Amasaya-Smuttha Vyadhi and Virechana for Pakvashya-Smuttha Vyadhi.This identification is done on the basis of physiological aspect of the body. The present article will explore the Shodhana aspects relating to the Udbhavasthana of Vyadhi as well as try to identify the therapeutic and prognostic significance of this understanding.